Natural compounds with anti-ageing activity - Argyropoulou, Aikaterini; Aligiannis, Nektarios; Trougakos, Ioannis P.; Skaltsounis, Alexios-Leandros (Natural Product ReportsNatural Product Reports, 2013)
Covering: up to the end of June 2013 Ageing is a complex molecular process driven by diverse molecular pathways and biochemical events that are promoted by both environmental and genetic factors. Specifically, ageing is defined as a time-dependent decline of functional capacity and stress resistance, associated with increased chance of morbidity and mortality. These effects relate to age-related gradual accumulation of stressors that result in increasingly damaged biomolecules which eventually compromise cellular homeostasis. Nevertheless, the findings that genetic or diet interventions can increase lifespan in evolutionarily diverse organisms indicate that mortality can be postponed. Natural compounds represent an extraordinary inventory of high diversity structural scaffolds that can offer promising candidate chemical entities in the major healthcare challenge of increasing healthspan and/or delaying ageing. Herein, those natural compounds (either pure forms or extracts) that have been found to delay cellular senescence or in vivo ageing will be critically reviewed and summarized according to affected cellular signalling pathways. Moreover, the chemical structures of the identified natural compounds along with the profile of extracts related to their bioactive components will be presented and discussed. Finally, novel potential molecular targets for screening natural compounds for anti-ageing activity, as well as the idea that anti-ageing interventions represent a systemic approach that is also effective against age-related diseases will be discussed. © The Royal Society of Chemistry.